Rational approaches, design strategies, structure activity relationship and mechanistic insights for therapeutic coumarin hybrids. Issue 16 (15th August 2019) - Singh, Harbinder; Singh, Jatinder Vir; Bhagat, Kavita; Gulati, Harmandeep Kaur; Sanduja, Mohit; Kumar, Nitish; Kinarivala, Nihar; Sharma, Sahil
Graphical abstract: Highlights: Rational approaches towards the design of pharmacologically active coumarin based hybrids. Structure-activity relationships and mechanistic insights for therapeutic coumarin hybrids. Chemotherapeutic potential of coumarin based hybrids. Coumarin hybrids as antioxidant and anti-Alzheimer's agents. Antidiabetic and anti-inflammatory activity of coumarin based hybrids. Abstract: Hybrid molecules, furnished by combining two or more pharmacophores is an emerging concept in the field of medicinal chemistry and drug discovery that has attracted substantial traction in the past few years. Naturally occurring scaffolds such as coumarins display a wide spectrum of pharmacological activities including anticancer, antibiotic, antidiabetic and others, by acting on multiple targets. In this view, various coumarin-based hybrids possessing diverse medicinal attributes were synthesized in the last five years by conjugating coumarin moiety with other therapeutic pharmacophores. The current review summarizes the recent development (2014 and onwards) of these pharmacologically active coumarin hybrids and demonstrates rationale behind their design, structure-activity relationships (SAR) and mechanistic studies performed on these hybrid molecules. This review will be beneficial for medicinal chemist and chemical biologist, and in general to the drug discovery community and will facilitate the synthesis and development of novel, potent coumarin hybrid molecules serving as lead molecules for the treatment of complex disorders.